Efficient and Secure Digital Signature Scheme for Post Quantum Epoch - Iavich, Maksim; Iashvili, Giorgi; Gnatyuk, Sergiy; Tolbatov, Andrii; Mirtskhulava, Lela (Information and Software Technologies, 2021)
It is expected the massive release of quantum computers in the near future. Quantum computers can easily break the crypto schemes, which are used in practice. Therefore, classical encryption systems have become vulnerable to quantum computer-based attacks. This involves the research efforts that look for encryption schemes that are immune to quantum computer-based attacks. This paper describes the digital signature schemes, which are safe against quantum computer attacks, but these schemes have different efficiency problems. The signature size of the scheme is very large and one-way function are used many time during the signature process. The paper offers the ways of reducing the signature size and acceleration the process of using one-way functions. It is offered to integrate the quantum key distribution algorithms into the scheme. It is also offered to use Blake family hash function as the one-way function.